An analysis of Sudan’s energy sector and its renewable energy potential in a comparative African perspective - Monged Abdalla (17542428) (2023)
The UN’s Sustainable Development Goals (SDGs) emphasize the importance of using reliable and clean energy at a reasonable cost (SDG 7). This article investigates Sudan’s renewable energy policies and the country’s potential to maximize renewable energy production. It argues that Sudan has great potential to secure a sustainable energy supply by switching to solar, wind, and geothermal resources. The central assumption is that Sudan’s diverse sources of renewable energy (RE) are not being exploited to their full capacity. The article highlights energy policies in other African countries that Sudan could adopt to expand RE generation. The analysis reveals promising indicators of Sudan’s ability to maximize its solar, wind, and geothermal energy resources. It also presents conclusions and recommendations concerning the future of RE policies and production in Sudan. Other Information Published in: International Journal of Environmental Studies License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/00207233.2023.2177417